Pengaruh Penambahan Tepung Tulang Ikan Gabus (Channa striata) terhadap Sifat Fisik dan Kimia Tortilla Jagung - Hidayat, Yessy Syahfitri; Rosidah, Umi (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Hidayat YS, Rosidah U. 2022. The effect of snakehead fish bones flour (Channa striata) on physical and chemical properties of corn tortilla. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 358-367. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).This study aimed to determine the effect of the concentration of the addition of snakehead fish bone meal on the physical and chemical properties of corn tortillas. The study used a completely randomized non-factorial design (RALNF) with one treatment factor and was repeated three times. The treatment factor was the concentration of addition of snakehead fish bone meal (0%, 2%, 4%, 6%, 8% and 10%). The parameters observed in this study were physical parameters (hardness and color) and chemical parameters (moisture content, ash content, calcium content and protein content). The results showed that the concentration of the addition of snakehead fish bone meal had a significant effect on hardness, color (lightness, redness, yellowness), moisture content, ash content, calcium content and protein content. The higher the concentration of snakehead fish bone meal used, the higher the value of hardness, ash content, calcium content and protein content while the water content will decrease. The color value shows a fluctuating graph due to the Maillard reaction during the frying process. The average value of hardness, ash content, calcium content and protein content increased based on the concentration treatment of snakehead fish bone meal 268,07 gf to 434,20 gf, 2,73% to 7,95%, 0,02 % to 3,62% and 11,21% to 20,16%. While the average value of the water content of corn tortillas decreased based on the addition of concentration treatment with the addition of snakehead fish bone meal by 6,99% to 1,97%.